2004
DOI: 10.2174/0929867043456034
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: From Dopamine to Glutamate and Back

Abstract: The first part of the present review describes the exciting journey of dopamine stabilizers, starting in the early eighties with the development of the partial dopamine agonist (-)-3-PPP of phenylpiperidine structure, via various compounds with aminotetraline structure with preferential autoreceptor antagonist properties, and then back again to phenylpiperidine compounds carrying substituents on the aromatic ring that transformed them from partial dopamine agonists to partial dopamine receptor antagonists, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 41 publications
4
96
0
1
Order By: Relevance
“…It has been suggested that the dysregulation of dopamine transmission in schizophrenia might be secondary to alterations in glutamatergic NMDA receptor-mediated transmission (Olney and Farber, 1995;Carlsson et al, 2004). A direct linkage between the two hypotheses has recently been shown in an experiment performed in healthy volunteers.…”
Section: Introductionmentioning
confidence: 96%
“…It has been suggested that the dysregulation of dopamine transmission in schizophrenia might be secondary to alterations in glutamatergic NMDA receptor-mediated transmission (Olney and Farber, 1995;Carlsson et al, 2004). A direct linkage between the two hypotheses has recently been shown in an experiment performed in healthy volunteers.…”
Section: Introductionmentioning
confidence: 96%
“…The catecholamine dopamine (DA) modulates both excitatory and inhibitory synaptic signaling (Dani and Zhou, 2004;Seamans and Yang, 2004) and in man plays a critical role in forebrain circuits implicated in motor and cognitive disorders (Reimherr et al, 1984;Crossman et al, 1987;Hernandez and Hoebel, 1988;Fiorino et al, 1993;Carlsson et al, 2004). An important mechanism of DA inactivation involves reuptake of DA by the presynaptic DA transporter (DAT) (Gainetdinov et al, 1998;BenoitMarand et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…6 The disability of schizophrenic patients is a composite of persistent positive symptoms, cognitive decline and mostly increasing negative symptoms over time, together with numerous features of general psychopathology. [1][2][3]7,8 The therapeutic application of dopamine antagonists, that is, antipsychotic drugs, 9 mainly addresses the 'tip of the iceberg', leading to a level of outside normality in these patients, which enables them and their environment to cope with the disease. With the newer generation of antipsychotics and their fewer side effects regarding extrapyramidal motor signs, patients' compliance, an essential factor for long-term prognosis, seemed to improve.…”
Section: Introductionmentioning
confidence: 99%